4-Hydroxybenzoic acid–1H-imidazole (1/1) - Wang, Wei (International Union of Crystallography, 2009)
In the title 1:1 adduct, C(7)H(6)O(3)·C(3)H(4)N(2), the crystal packing features π–π stacking interactions [centroid–centroid distances = 3.799 (2) and 3.753 (1) Å] as well as N—H⋯(O,O) O—H⋯O and C—H⋯O hydrogen bonds.